Prototype development of thermoelectric generator system for exhaust heat recovery of an automobile - Said, M.A. (Asian Research Publishing Network, 2016)
In this study, a Thermoelectric Generator System (TEG) for exhaust heat recovery was developed and tested in a commercial small passenger automobile. The current phase of development is still in prototype mode, where the TEG was designed and then tested in a Perodua Myvi car in an idle condition. The main components of the designed TEG system consist of heat source recovery, insulator, TEG panel and heat sink. The TEG was placed at the ideal location on the exhaust system based on the optimum temperature condition of the TEG panel which is in the range of 150-250Â°C and sufficient space for the TEG system. Based from the TEG performance test results, it indicates that for an idle car condition, the maximum power output of 36.4 W can be obtained. A MATLAB Simulink simulation was performed to predict the extent of TEG performance in the Perodua Myvi car with driving condition under a variable load of an urban daily drive schedule (UDDS) cycle. The simulation results shows that the TEG system can produce an average of 258 W of power output and the total amount of energy recovered is 7, 586 kJ/cycle. In comparison with the estimated amount of waste heat dissipated in exhaust gas, only 4.7 percent of energy is recovered. However, the amount of power produced is sufficient to provide auxiliary power requirement for some of the electrical systems in the vehicle. Â©2006-2016 Asian Research Publishing Network (ARPN).